A cross-sectional survey of public knowledge of the monkeypox disease in Nigeria - Ahmad Ibrahim Al-Mustapha; Oluwaseun Adeolu Ogundijo; Nafisah Ayinde Sikiru; Barakat Kolawole; Muftau Oyewo; Hager El-Nadi; Ashiru Mohammed Mustapha; Lucky Icomiare Adebudo; Adesoji Odukoya; Emmanuella Chinenye Asiegbu; Magdalene B. Nanven; Taibat Lawal-Atolagbe; et al. (BMC Public Health, 2023)
Abstract The Monkeypox Disease (MPXD) gained attention due to its widened geographical distribution outside of Africa, Hence, a it was declared a global health emergency. The index case in Europe was from a Nigerian traveller. This study assessed public awareness and knowledge of the MPXD by conducting an online, cross-sectional survey of educated Nigerians. A total of 822 respondents were recruited using the snowball sampling method between the 16th to 29th of August 2022. More responses were retrieved from the Northeastern geopolitical region (30.1%, n=220) than other regions. Descriptive statistics revealed that 89% (n=731/822) of the study participants were aware of the MPXD but only 58.7% (n=429/731) of them had good knowledge of the disease with a mean knowledge score of 5.31±2.09. The main knowledge gaps were in the incubation period of the disease, the signs and symptoms, its mode of transmission, and preventive practices needed to curb the spread of the monkeypox virus (MPXV). Specifically, only 24.5% (n=179) of them knew that MPXV can be transmitted via sexual contact. Most of the study participants (79.2%, n=651) opined that we can prevent the occurrence of public health emergencies in the future. The multivariable logistic regression analysis revealed that of the socio-demographic variables, the male gender (OR: 1.69; 95% CI: 1.22,2.33); Ph.D. level education (1.44; 95% CI: 1.048,4.23); and being homosexual (OR:1.65; 95% CI: 1.07,3.78) were significantly associated with good knowledge of MPXD. Despite the varying prevalence across the country, the region of residence within Nigeria did not influence the knowledge of MPXD among the respondents. The knowledge gaps necessitate intensified public health risk communication with a focus on modes of transmission and the preventive measures needed to curb the spread of the MPXV.